2019
DOI: 10.1016/j.cbpb.2018.09.003
|View full text |Cite
|
Sign up to set email alerts
|

A complete enzymatic capacity for long-chain polyunsaturated fatty acid biosynthesis is present in the Amazonian teleost tambaqui, Colossoma macropomum

Abstract: In vertebrates, the essential fatty acids (FA) that satisfy the dietary requirements for a given species depend upon its desaturation and elongation capabilities to convert the C18 polyunsaturated fatty acids (PUFA), namely linoleic acid (LA, and α-linolenic acid (ALA, 18:3n-3), into the biologically active long-chain (C20-24) polyunsaturated fatty acids (LC-PUFA), including arachidonic acid (ARA, 20:4n-6), eicosapentaenoic acid (EPA, 20:5n-3) and docosahexaenoic acid (DHA, 22:6n-3). Recent studies have establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 62 publications
(86 reference statements)
7
44
0
Order By: Relevance
“…To date, only one exception to this pattern has been reported in the Japanese eel Anguilla japonica, a basal teleost that possesses a Fads1 with ∆5 desaturase capacity (Lopes-Marques et al 2018). More commonly though, teleostei Fads2 is functionalised during expansion of teleosts and Fads2 with Δ6 (Zheng et al 2004(Zheng et al , 2009González-Rovira et al 2009;Mohd-Yusof et al 2010;Monroig et al 2010aMonroig et al , 2013aKabeya et al 2018b), dual Δ6 andΔ5 (Hastings et al 2001;Tanomman et al 2013;Fonseca-Madrigal et al 2014;Kuah et al 2016;Oboh et al 2016;Ferraz et al 2018), Δ5 (Abdul Hamid et al 2016) and Δ4 (Li et al 2010;Morais et al 2012;Fonseca-Madrigal et al 2014;Oboh et al 2017a) desaturase activities have been identified. Like mammalian FADS2 (Park et al 2009), teleost Fads2 typically show Δ8 desaturase activity (Monroig et al 2011a), enabling the initiation of the longchain PUFA biosynthetic pathways via the so-called "Δ8 pathway", an alternative route to the "Δ6 pathway" (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, only one exception to this pattern has been reported in the Japanese eel Anguilla japonica, a basal teleost that possesses a Fads1 with ∆5 desaturase capacity (Lopes-Marques et al 2018). More commonly though, teleostei Fads2 is functionalised during expansion of teleosts and Fads2 with Δ6 (Zheng et al 2004(Zheng et al , 2009González-Rovira et al 2009;Mohd-Yusof et al 2010;Monroig et al 2010aMonroig et al , 2013aKabeya et al 2018b), dual Δ6 andΔ5 (Hastings et al 2001;Tanomman et al 2013;Fonseca-Madrigal et al 2014;Kuah et al 2016;Oboh et al 2016;Ferraz et al 2018), Δ5 (Abdul Hamid et al 2016) and Δ4 (Li et al 2010;Morais et al 2012;Fonseca-Madrigal et al 2014;Oboh et al 2017a) desaturase activities have been identified. Like mammalian FADS2 (Park et al 2009), teleost Fads2 typically show Δ8 desaturase activity (Monroig et al 2011a), enabling the initiation of the longchain PUFA biosynthetic pathways via the so-called "Δ8 pathway", an alternative route to the "Δ6 pathway" (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In fish, Elovl5 enzymes can efficiently elongate C 18 and C 20 PUFA, with remarkably lower elongase capacity towards C 22 substrates (Castro et al 2016). Elovl2, an enzyme with C 20 and C 22 PUFA as preferred elongation substrates, exists in some fish (Monroig et al 2009;Morais et al 2009;Oboh et al 2016;Ferraz et al 2018), but it was lost during expansion of teleosts and is absent in recently emerged teleost lineages (Castro et al 2016). Teleost Elovl4, along with its role in the biosynthesis of very long-chain (> C 24 ) PUFA (Monroig et al 2010b), can elongate C 22 PUFA like Elovl2 and thus has been hypothesised to somewhat compensate for the loss of Elovl2 in some teleosts (Monroig et al 2011b;Kabeya et al 2015;Jin et al 2017;Oboh et al 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…In the phylogenetic tree, B. boddarti Elovl is placed within the Elovl5 clade, which is distinct from Elovl2 and Elovl4. This clade, supported by an elongase from a lamprey species, comprises several functionally characterised Elovl5 from the relatively ancient salmonids and ostariophysians (Agaba et al ., 2004; Agaba et al ., 2005; Carmona‐Antonanzas et al ., 2013; Ferraz et al ., 2019; Morais et al ., 2009) and a larger clade represented by the species‐rich modern percomorphs (Kabeya et al ., 2015; Kuah et al ., 2015; Monroig et al ., 2013). In addition, orthologs from B. pectinirostris , P. schlosseri and P. magnuspinnatus were clustered with the B. boddarti Elovl5.…”
Section: Discussionmentioning
confidence: 99%
“…In the phylogenetic tree, B. boddarti Elovl is placed within a Elovl5 clade, distinct from the Elovl2 and Elovl4 clades. The Elovl5 clade, supported by an elongase from a lamprey species, comprises of several functionally characterised Elovl5 from the relatively ancient salmonids and ostariophysians (Agaba et al, 2004, Agaba et al, 2005, Morais et al, 2009, Carmona-Antonanzas et al, 2013, Ferraz et al, 2019) and a large clade represented by the species-rich modern percomorphs (Kuah et al, 2015, Kabeya et al, 2015, Monroig et al, 2013). This suggests the cloned B. boddarti elongase is an ortholog of the Elovl5 family.…”
Section: Discussionmentioning
confidence: 99%
“…In most teleost, the Elovl5 elongates C18 and C20 PUFA at much higher rate than C22 PUFA, with the latter often at conversion rate of below 5%. While the capacity to elongate C22 PUFA seemed exclusive to Elovl2 rather than Elovl5, this paralog has only been isolated and characterised from salmonids and several clupeocephalan species (Agaba et al, 2004, Morais et al, 2009, Oboh et al, 2016, Machado et al, 2018, Ferraz et al, 2019). To date, elov5 from two euryhaline herbivorous species, spotted scat ( Scatophagus argus ) and rabbitfish ( Siganus canaliculatus ) have been reported to have moderate but measurable elongation capacity of C22 substrates (Monroig et al, 2012, Xie et al, 2016).…”
Section: Discussionmentioning
confidence: 99%